Study of factors of utilisation of antenatal services and awareness among pregnant women in third trimester attending government maternity hospital Warangal, Telangana State, India - Niharika, L.; Bhavani, K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Understanding the factors affecting the utilization of maternity care during pregnancy and delivery is required. The present study was carried out to find out the awareness and factors associated with utilization of maternal care services. Methods: A community based observational study was conducted during September to November 2015 on randomly selected antenatal mothers attending Government Maternity hospital, Kakatiya Medical College, Warangal, India. A total of 200 third trimester pregnant women were interviewed using a pre-tested questionnaire regarding utilization and awareness of antenatal services. Statistical analysis: Percentages, Proportions and chi-square test. Results: A total of 200 antenatal mothers participated in the study. Majority (37.5%) belonged to the age group of 20-24 years in which most of the antenatal mothers belong to Hindu religion (86.3%), of which 50.7% lived in a nuclear family. In this study, the percentage of antenatal mother belonging to Upper Lower class was predominant with 26.5%. Association was also found regarding utilization of antenatal services between age of the mother and literacy of the mother. 83.5% of the antenatal mothers had taken the recommended two doses of T.T with a complete booster dose, 87.1% are aware of family planning services, 97.8% of antenatal mothers are aware of immunization and approximately 95% of the antenatal mothers are aware of mother craft classes. Conclusions: The study shows early and wide spread use of antenatal care, but it also reveals that the antenatal visits occur late in the pregnancy. The literacy and age of women has significant bearing on utilization of antenatal care by the pregnant women.